Meropenem utilization evaluation in a referral teaching hospital in Iran - Peyman Naderi; Kiana Shirani; Rasool Soltani; Farzin Khorvash; Seyed Saeed Naji Esfahani (Wolters Kluwer Medknow Publications, 2018)
Objective: Inappropriate use of antibiotics is associated with detrimental effects including emergence of antibiotic resistance. This study aimed to evaluate the use of meropenem, an extended-spectrum antibiotic, in a referral teaching hospital to detect different types of errors in its prescription. Methods: In a cross-sectional study performed over a 6-month period (2014-2015), hospitalized adult patients who received meropenem for any indication were randomly selected. The collected data included the indication for prescription and its correctness, the basis of prescription (empirical or culture based), administered dose, duration of treatment, the status of demanding sample culture in the case of empirical prescription, the status of dose adjustment in the case of renal impairment, and the treatment outcome. Findings: Over the study period, 123 patients were evaluated. The most frequent indication for prescription of meropenem was pneumonia (31.7%) and soft-tissue infections (18.7%). Out of these prescriptions, 62.6% (77 prescriptions) were incorrect. All meropenem prescriptions were initially empirical. Furthermore, sample culture and antibiotic susceptibility test were requested for only 52% of patients (n = 66). Treatment duration was correct for 53.7% of patients. Seventeen patients (13.8%) received an inappropriate dose of the antibiotic. Furthermore, of 51 patients who needed meropenem dose adjustment because of renal impairment, 17 patients (33.33%) received unadjusted dose. Conclusion: High rate of errors exists in the utilization of meropenem in our hospital, especially in the rank order of selection for treatment (indication), dose adjustment, and treatment duration. Therefore, modification strategies are necessary to promote the rational use of meropenem in this center.